Small crimes in small playing forms - Alexandrova, Petia (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
The text is focused on Bulgarian short films from the last years, which deal with the sins of their characters, mainly without punishment. In one option, a dramatic event is chosen – death, usually not caused by the hero, as a key to any questions and feelings. That’s why in „Linda“, „Dog“, „Antigone“, „Hole“, the funeral is a major story pillar. In the other option, the focus is on the little crime, „so little that you can not forget it all day.“ Small bands and stories, pre-scene behind-the-scenes, and the possibility of watching and skepticism („Snail“,“Shame“,“Morning Coffee“, „Robbery“). In the short films, opposite to the full features, the end is often positive – the goodness triumphs. Which is not only film but also life position.